A zebrafish model for studying the mechanisms of newborn hyperbilirubinemia and bilirubin-induced neurological damage - Guzelkaya, Metehan; Onal, Ebru; Gelinci, Emine; Kumral, Abdullah; Cakan-Akdogan, Gulcin (Frontiers in Cell and Developmental Biology, 2023)
Unresolved neonatal hyperbilirubinemia may lead to the accumulation of excess bilirubin in the body, and bilirubin in neural tissues may induce toxicity. Bilirubin-induced neurological damage (BIND) can result in acute or chronic bilirubin encephalopathy, causing temporary or lasting neurological dysfunction or severe damage resulting in infant death. Although serum bilirubin levels are used as an indication of severity, known and unknown individual differences affect the severity of the symptoms. The mechanisms of BIND are not yet fully understood. Here, a zebrafish newborn hyperbilirubinemia model is developed and characterized. Direct exposure to excess bilirubin induced dose- and time-dependent toxicity linked to the accumulation of bilirubin in the body and brain. Introduced bilirubin was processed by the liver, which increased the tolerance of larvae. BIND in larvae was demonstrated by morphometric measurements, histopathological analyses and functional tests. The larvae that survived hyperbilirubinemia displayed mild or severe morphologies associated with defects in eye movements, body posture and swimming problems. Interestingly, a plethora of mild to severe clinical symptoms were reproduced in the zebrafish model.